The behavior of external debt in Asian countries: evidence based on panel unit root test - Evan, Lau; Ahmad Zubaidi, Baharumshah; Siew-Voon, Soon (Taylor & Francis, 2013)
This article investigates the mean-reverting behavior of the external debt ratio based on a clustered of 19 Asian countries from 1981 to 2010. For this purpose, we use a government’s intertemporal budget constraint (GIBC) model popularized by Hamilton and Flavin (1986). Our conclusions were drawn from panel data based tests, including the newly developed test that accounts for both cross-sectional dependency and structural breaks. Two major findings are noteworthy; first majority debt ratios in the Asian countries are affected by structural breaks. Second, we find unit root tests that do not accommodate breaks are less likely to detect mean reversion in the debt ratios. In all, our results indicate debt sustainability is a general characteristic of all the Asian countries.